Discovery of a phenylpyrazole amide ROCK inhibitor as a tool molecule for in vivo studies. Issue 21 (1st November 2020) - Hu, Zilun; Wang, Cailan; Glunz, Peter W.; Li, Julia; Cheadle, Nathan L.; Chen, Alice Y.; Chen, Xue-Qing; Myers, Joseph E.; Guarino, Victor R.; Rose, Anne; Sack, John S.; Sitkoff, Doree; et al.
Graphical abstract: Highlights: SAR optimization is explored on a series of phenylpyrazole amides in the discovery of dual ROCK1 and ROCK2 inhibitors. ROCK1 and ROCK2 co-crystal structures of a dual inhibitor are described. An in vivo tool molecule which demonstrates good potency, kinome selectivity, and favorable pharmacokinetic profile is identified. The tool molecule is evaluated for hemodynamic effects in telemeterized mice, from which moderate decreases in blood pressure are observed. Abstract: Structure-activity relationship optimization on a series of phenylpyrazole amides led to the identification of a dual ROCK1 and ROCK2 inhibitor (25 ) which demonstrated good potency, kinome selectivity and favorable pharmacokinetic profiles. Compound 25 was selected as a tool molecule for in vivo studies including evaluating hemodynamic effects in telemeterized mice, from which moderate decreases in blood pressure were observed.